PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERRHADAP KEMAMPUAN BERFIKIR KRITIS PADA MATERI TRIGONOMETRI SISWA KELAS XI SMAN 15 ADIDARMA BANDA ACEH - Mushalli Rosalina; Bansu Irianto Ansari; Mik Salmina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students’ critical thinking skills, especially in the topic of Trigonometry. Most students tend to focus only on memorizing formulas without trying to understand them. One of the contributing factors is the use of conventional teaching methods that are still teacher-centered, such as lectures, exercises, and assignments, which limit students’ opportunities to think critically. One learning model that can be used to enhance students’ critical thinking skills is the Cooperative Learning Model of the Think Pair Share type. The purpose of this study is to determine the effect of the Cooperative Learning Model of the Think Pair Share type on improving the critical thinking skills of eleventh-grade students at SMA Negeri 15 Adidarma Banda Aceh in the topic of Trigonometry. This study uses a quantitative approach with an experimental method, employing a one-group pre-test and post-test design. The population consists of all eleventh-grade students, with a sample of 20 students from class XI-1. Data collection was conducted through a critical thinking skills test, which was then analyzed using statistical tests. The results of the study show that the average pre-test score was 46, while the average post-test score was 69.95. Based on the results of a simple linear regression test, the equation obtained is ŷ = a + bX or ŷ = 51.897 + 0.393X. The constant value is positive (51.897), indicating that the independent variable (X) has a significant effect on the dependent variable (Y).